Community Service Order as the Embodiment of Social Justice Values in the Indonesian Penal System - Didik Purnomo; Anis Widyawati; Rasdi Rasdi (Fakultas Hukum Universitas Lampung, 2025)
Community Service Order an alternative sentencing aimed at reducing dependence on imprisonment while restoring social balance within the community. This study examines how the Community Service Order can represent the values of social justice as reflected in the fifth principle of Pancasila. The study analyzed the philosophical, juridical, and penological bases of Community Service Order as well as its legal implications within the framework of the 2023 Criminal Code. In this juridical-normative study, philosophical and penological approaches were used based on the analysis of legislation, legal literature, and the thoughts of criminal law experts. The results show that Community Service Order has the potential to balance community protection, victims' interests, and offender rehabilitation. In addition, this punishment reflects the values of distributive and corrective justice in line with the principles of social justice in Pancasila. Therefore, Community Service Order does not only function as an alternative sanction but also as a criminal policy instrument that supports the development of a more humane, restorative, and socially just Indonesian penal system.